Newborn Hearing Screening in Neonates Exposed to Psychoactive Drugs - Rocha, Bruna Salazar Castro da; Machado, Márcia Salgado; Zanini, Cláudia Fernandes Costa; Paniz, Tatiana de Carvalho; Menegotto, Isabela Hoffmeister (International Archives of Otorhinolaryngology, 2014)
Introduction In pregnancy, the mother and fetus share body structures based on the maternal organism. Exposure to psychoactive drugs in this period may have repercussions on the baby's hearing. Therefore, it is necessary to investigate this association.Aim Analyze the results of newborn hearing screening (NHS), the occurrence of associated risk factors, and the incidence of hearing loss in newborn exposed to psychoactive drugs during pregnancy.Methods This is an observational retrospective study done from a database analysis. From this database, records were selected about the use of psychoactive drugs by mothers during pregnancy, then the neonates were divide into two groups: the study group (146 babies exposed to drugs) and the control group (500 babies not exposed to drugs). The NHS failure rate, the presence of risk factors for hearing loss, and need for audiological diagnosis were analyzed in both groups. From these variables, absolute frequency and prevalence rates were calculated and the results compared between groups.Results There was no statistically significant difference in the comparison of NHS failure rates between the groups (p = 0.267). The occurrence of risk factors for hearing loss was greater in babies exposed to drugs (p < 0.0001). There was only one diagnosis of hearing loss, which occurred in the control group (p = 0.667).Conclusion The use of psychoactive drugs by mothers during pregnancy did not affect the NHS failure rate of this sample. However, the occurrence of significant risk factors in the study group showed a possible sensitivity of babies exposed to psychoactive drugs during pregnancy.
Keywords: newborn screening; psychotropic drugs; hearing